As representações sociais da Política Nacional de Saúde da Pessoa Idosa : uma análise à luz do campo da ciência, tecnologia e sociedade - Silva, Meliza Cristina da (2016)
The aging and the consequent Brazilian demographic change point us to a profound socio-economic transformation of the country. It is estimated that the elderly population will triple in the coming decades, from 20 million in 2010 to 65 million in 2050. Many actors are responsible for implementing the National Health Policy for the Elderly, among them are the local health managers and articulators health of the elderly. The aim of this study is to analyze the social representations of the National Health Policy for the Elderly in a regional health department, the light field of science, technology and society. This is a qualitative, exploratory and descriptive. The methodological approach was to document analysis and field exploration, through semi-structured interviews. The results point to incipient front practices to a well-structured policy, the social representations of groups influence their deployment. Low public participation, especially the elderly and the distancing of the research to the practice of these municipalities are short of expectations of policy. The field of science, technology and society contributes to reflections on the appropriation of science and technology, it was observed that in his views prevail the harsh health technologies. The intention of this thesis was to analyze the policy and practices in the current scenario, with no claim assessment, was intended to bring reflections on this policy by the look of social representations and studies of science, technology and society We can conclude that the regions implement the National Policy differently, with demands and perceptions appropriate to their reality, even if they receive national and international guidelines.